EVALUASI JUMLAH DAN BIAYA OPERASIONAL ALAT BERAT PADA PROYEK REVITASLISASI SUNGAI (Studi Kasus Proyek CWP – 3DJK Wulan River Improvement Works Package III, BBWS Pemali–Juana, Kabupaten Demak–Kudus–Jepara, Jawa Tengah) - Khomsiati, Nur Latifah; Cahyono, Heru Setiyo; Ihwalrezky, Zhagheta; Saefudin, Ruli (Journal Innovation of Civil Engineering (JICE), 2025)
This study evaluates the quantity and operational costs of heavy equipment in the Wulan River Revitalization Project (CWP–3DJK) across Demak, Kudus, and Jepara, aiming to identify factors hindering efficiency and performance. Using a mixed–methods case study (quantitative analysis, field observations, interviews, and document reviews), results show Excavator productivity dropped 14.3% from theoretical standards (12.67 m³/hour vs. 14.57 m³/hour), mainly due to 22% non–technical downtime from heavy rainfall, excessive sedimentation, and social conflicts. Operational costs exceeded the budget by 12.5% (Rp. 14.8 billion), driven by fuel (42%) and emergency maintenance on muddy terrain. Equipment imbalance (4 Excavators vs. 11 dump trucks) caused loading queues, reducing dump truck efficiency by 18%. Constraints included technical (sedimentation), environmental (rainfall), and social (protests), with social factors contributing 18% downtime—often overlooked in past studies. Recommendations include swamp–type excavators, 10–15% contingency funds in the Budget Plan (QS), and community dialogue forums to reduce conflicts. Practical benefits include improved budget efficiency (<5% deviation), reduced social downtime, and IoT–based real–time monitoring. Findings emphasize the need for an integrated approach combining technical, environmental, and community participation to ensure sustainable infrastructure project success in Indonesia. Keywords: Heavy Equipment; Operational Costs; River Revitalization; Productivity; Project Management.